Semiotika Batik Larangan di Yogyakarta - Rina Patriana Chairiyani (Humaniora, 2014)
Batik is a part of Indonesian heritage and culture. In Yogyakarta, there is known as Batik Larangan. The pattern of this Batik is used as identity and status. For the Javanese, Batik is not just a fashion; moreover, it contains philosophy and beliefs closely related to daily life. Batik also becomes identic to the greatness of the leader that considers having a power to increase his authority. By using qualitiative methodology, this study writes about how the semiotic concept can be used on art and culture study in Javanese people.